Longitudinal analysis of ESBL and carbapenemase carriage among Enterobacterales and Pseudomonas aeruginosa isolates collected in Europe as part of the International Network for Optimal Resistance Monitoring (INFORM) global surveillance programme, 2013–17. (10th February 2020) - Kazmierczak, Krystyna M; de Jonge, Boudewijn L M; Stone, Gregory G; Sahm, Daniel F
Abstract: Objectives: To determine the spread of ESBLs and carbapenemases in Enterobacterales and Pseudomonas aeruginosa in Europe. Methods: 45 335 Gram-negative bacilli were collected in 18 European countries as part of the International Network for Optimal Resistance Monitoring (INFORM) global surveillance programme from 2013 to 2017. Antimicrobial susceptibility was determined using broth microdilution, and 9546 isolates were screened for β-lactamase genes by PCR and sequencing. Results: ESBLs were identified in 35.5% of Klebsiella pneumoniae and 18.5% of Escherichia coli . ESBL carriage was lowest among isolates in Northern/Western Europe and highest in Eastern Europe. CTX-M-15 was the dominant ESBL in all countries except Greece, where SHV-type ESBLs were more common. Carbapenemases (KPC, OXA-48-like, GES, NDM and VIM) were found in 3.4% of Enterobacterales and were most common among K. pneumoniae (10.5% of those collected). Carbapenemase carriage was lowest in Northern/Western and highest in Southern Europe. KPC-positive Enterobacterales were most abundant but the percentages of OXA-48-like-, NDM- and VIM-positive isolates increased over time and were correlated with an increase in meropenem non-susceptibility. Carbapenemases (VIM, IMP, NDM and GES) were also identified in 5.1% of P. aeruginosa and were commonly found in Eastern Europe. Carbapenemase carriage and meropenem non-susceptibility among P. aeruginosa fluctuated over the 5 years studied and were not well correlated. Conclusions: ESBL and carbapenemase carriage varied by species and European subregion. Meropenem non-susceptibility in European isolates of Enterobacterales can be attributed to carbapenemase carriage and is increasingly caused by MBLs and OXA-48-like carbapenemases. Carbapenemases or other β-lactamases are not a common cause of meropenem non-susceptibility in P. aeruginosa in Europe.